Cardiac amyloidosis‐A review of current literature for the practicing physician. Issue 3 (17th February 2021) - Ash, Samantha; Shorer, Eran; Ramgobin, Devyani; Vo, Maique; Gibbons, Jonathan; Golamari, Reshma; Jain, Rahul; Jain, Rohit
Abstract: The amyloidoses are a family of diseases in which misfolded precursor proteins aggregate to form amyloid and deposit in body tissues. A very serious yet underrecognized form of this disease is cardiac amyloidosis, in which amyloid deposits into the extracellular space of the myocardium, resulting in thickening and stiffening of ventricular walls with resultant heart failure and conductive dysfunction. This review provides a discussion of the pathogenesis and clinical presentation of cardiac amyloidosis subtypes, as well as an up‐to‐date approach to diagnosis and treatment. Significant progress has been made in recent years regarding diagnosis and treatment of this condition, but prognosis remains heavily reliant on early detection of the disease. Two types of precursor protein are responsible for most cardiac amyloidosis cases: transthyretin amyloid, and immunoglobulin‐derived light chain amyloid. An early diagnosis of cardiac amyloidosis can allow for novel treatment modalities to be initiated with the potential to improve prognosis.